El turismo internacional como determinante del crecimiento económico en Colombia : un análisis de 2006 a 2018 (2019)
The International tourism in Colombia is experiencing a historic boom. An example of this is the unprecedented arrival of 4.2 million travelers in 2018. This research investigates about the impacts of tourism on Colombian economic growth between 2006 and 2018. For this purpose, this work explores the incidence of competitiveness channels and the importation of capital goods. Methodologically, this research analyzes the stationarity of the data, performs cointegration tests, applies the Granger causality test and analyzes impulse response functions. The results suggest that, in the long term, there is a stable and positive relationship in which the growth rates of tourist arrivals, which are close to 10%, are related to rates of 0.48% in GDP growth. However, contrary to intuition, the direction of the relationship is growth-tourism. In the short term, there are no positive effects of tourism on growth. The results agree with previous findings in Colombia in terms of the relationship but not of the causality. This implies that the economic reactivation and positioning of Colombia as an international destination, through infrastructure and capacity, are the way to obtain the greatest long-term benefit of tourism for the economy.